Hubungan Kebersihan Diri dan Keluhan Gangguan Kulit Pada Petani - Nia Niken Tinungki; I Gede Purnawinadi (NUTRIX, 2023)
Personal hygiene is one way for individuals to maintain their health in achieve physical and psychological well-being. Poor personal hygiene can cause problems with skin health, in the form of redness, itching, scaly, burning sensation, and occurs naturally directly. This study aims to determine the relationship between personal hygiene and complaints of skin disorders among farmers in Lolak Village. The research method used is a descriptive correlation with a cross-sectional approach. The sample size in this study was 240 respondents taken using a purposive sampling technique. Variable data was collected using a questionnaire. The research results showed that of the 240 respondents, there were 219 (91.25%) respondents with poor personal hygiene and the majority of respondents experienced the 3 most common complaints of skin disorders, namely redness, itching, and natural skin complaints that occurred directly. The results of the analysis using the Spearman Rank statistical test showed a p-value = 0.100 > 0.05, which means there is no significant relationship between personal hygiene and complaints of skin disorders among farmers in Lolak Village. It is hoped that farmers in Lolak Village can improve their personal hygiene. For further research, it is recommended to research topics related to environmental sanitation, knowledge, and the use of personal protective equipment. Keywords: Complaints of Skin Disorders, Personal hygiene, Farmers. Abstrak Kebersihan diri adalah salah satu cara individu untuk memelihara kesehatannya dalam mencapai fisik dan psiokologis yang sejahtera. Kebersihan diri yang tidak baik dapat mengakibatkan gangguan pada kesehatan kulit, berupa kemerahan, gatal-gatal, bersisik, seperti rasa terbakar, dan terjadi alami secara langsung. Penelitian ini bertujuan untuk mengetahui hubungan kebersihan diri dengan keluhan gangguan kulit pada petani di Desa Lolak. Metode penelitian yang digunakan yaitu deskriptif korelasi dengan pendekatan cross sectional. Besar sampel dalam penelitian ini yaitu 240 responden yang diambil melalui teknik purposive sampling. Data variabel dikumpul menggunakan kuesioner. Hasil penelitian menunjukkan dari 240 responden terdapat 219 (91,25%) responden dengan kebersihan diri yang tidak baik serta sebagian besar responden mengalami 3 keluhan gangguan kulit terbanyak yaitu kemerahan, gatal-gatal dan keluhan kulit alami terjadi secara langsung. Hasil analisis dengan menggunakan uji statistik spearman rank menunjukkan hasil p-value = 0,100 > 0,05 yang berarti tidak ada hubungan yang signifikan antara kebersihan diri dengan keluhan gangguan kulit pada petani di Desa Lolak. Diharapkan bagi petani di Desa Lolak dapat meningkatkan kebersihan diri. Bagi penelitian selanjutnya direkomendasikan untuk meneliti topik terkait sanitasi lingkungan, pengetahuan, serta penggunaan APD. Kata Kunci: Kebersihan diri, Keluhan Gangguan Kulit, Petani.